War and public health - Levy, Barry S.; Sidel, Victor W. (New York ; Oxford : Oxford University Press, 2008)
An examination of the relationship between war and public health, this book documents the public health consequences of war and describes what health professionals can do to minimise these consequences and even help prevent war altogether. It explores the effects of war on health, human rights, and the environment.
Previous ed.: 1997.
Description based on print version record.
Includes bibliographical references and index.
Keywords: War -- Medical aspects; Public health; War and society